(untitled) (International Journal of Engineering and Computer Science, 2015)
With the advent of service computing and cloud computing, more and more services are emerging on the Internet, generating huge volume of data. The overwhelming service-generated data become too large and complex to be effectively processed by traditional approaches. How to store, manage, and create values from the service-oriented big data become an important research problem. On the other hand, with the increasingly large amount of data, a single infrastructure which provides common functionality for managing and analyzing different types of service-generated big data is urgently required.